2012
DOI: 10.1111/j.1365-2141.2012.09082.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti‐myeloma activity of TRAIL‐expressing adipose‐derived mesenchymal stem cells

Abstract: SummaryRecently, genetically modified mesenchymal stem cells (MSCs) have been exploited to deliver anti-cancer bio-drugs directly within the tumour mass. Here, we explored whether adipose-derived MSCs (AD-MSCs), engineered to express the pro-apoptotic ligand TRAIL (also known as TNFSF10), kill multiple myeloma (MM) cells and migrate towards MM cells in vitro. Different MM cell lines were assessed for their sensitivity to recombinant human (rh) TRAIL alone and in combination with the proteasome inhibitor bortez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…To date, adult MSCs ''armed'' by genetic engineering have been used to target MM cells in a few pioneering cytotherapy approaches [29]. BM-MSCs induced to overexpress Fas-L or IFN-a have been successfully applied to induce apoptosis in MM cells [13,56], while we have recently proved that AD-MSCs, engineered to stably overexpress the membrane form TRAIL, trigger a remarkable apoptosis of MM cells in vitro [14], thus improving the therapeutic efficacy of TRAIL in MM. This study, however, indicates that UC-MSCs possess a constitutive ability to control malignant plasma cell growth both in vitro and in vivo by paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, adult MSCs ''armed'' by genetic engineering have been used to target MM cells in a few pioneering cytotherapy approaches [29]. BM-MSCs induced to overexpress Fas-L or IFN-a have been successfully applied to induce apoptosis in MM cells [13,56], while we have recently proved that AD-MSCs, engineered to stably overexpress the membrane form TRAIL, trigger a remarkable apoptosis of MM cells in vitro [14], thus improving the therapeutic efficacy of TRAIL in MM. This study, however, indicates that UC-MSCs possess a constitutive ability to control malignant plasma cell growth both in vitro and in vivo by paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a suppressive activity of MSCs on MM cell growth has also been reported, both in vitro and in animal models of the human disease [13]. We have recently demonstrated that AD-MSCs stably engineered to express the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) efficiently migrate toward MM cells and exert anti-MM cytotoxicity in vitro [14], while others showed that MM-bearing SCID-rab mice injected with placenta-derived MSCs underwent dramatic inhibition of tumor growth within the bone [15].…”
Section: Introductionmentioning
confidence: 99%
“…When injected into mice, AD-MSC-TRAIL migrated to tumors and induced apoptosis in tumor cells, without significant toxicities to normal tissues (Grisendi et al, 2010). In a similar study, AD-MSCs engineered to express TRAIL were found to exhibit antimyeloma activities and significantly induce myeloma cell death in vitro (Ciavarella et al, 2012).…”
Section: Stem Cell -Proapoptotic Protein Therapymentioning
confidence: 85%
“…When injected into mice, AD MSC-TRAIL migrated to tumors and induced apoptosis in tumor cells, without significant toxicities to normal tissues [131]. In a similar study, AD MSC engineered to express TRAIL was found to exhibit anti-myeloma activities and significantly induce myeloma cell death in vitro [132].…”
Section: Pro-apoptotic Proteinsmentioning
confidence: 87%